Considerations on a mutation in the NOTCH3 gene sparing a cysteine residue: a rare polymorphism rather than a CADASIL variant - Bersano, Anna (CIC Edizioni Internationali, 2013)
Some missense mutations and small deletions in the NOTCH3 gene, not involving cysteine residues, have been described in patients considered to be affected by paucisymptomatic CADASIL. However, the significance of such molecular variants is still unclear. We describe a 49-year-old woman with a CADASIL-like phenotype, carrying a novel cysteine-sparing mutation in exon 29 of the NOTCH3 gene, and discuss the possible pathogenetic role of this molecular variant. Even though atypical clinical and MRI findings make a diagnosis of CADASIL unlikely in this patient, our report nevertheless underlines the intriguing genotype-phenotype relationship in NOTCH3 mutations and the importance of functional investigation to ascertain the role of new NOTCH3 mutations in CADASIL pathogenesis.